2012
DOI: 10.21273/hortsci.47.9.1351
|View full text |Cite
|
Sign up to set email alerts
|

Response of Selected Wildflower Species to Saline Water Irrigation

Abstract: Wildflowers are good candidates for water-wise landscapes because many of them are drought-tolerant after establishment. Little information is available regarding whether these herbaceous wildflowers are tolerant to salt stress. Container experiments were carried out in a greenhouse and a shadehouse under semiarid climate conditions to investigate the salt tolerance of six native wildflowers: Salvia farinacea (mealy cup sage), Berlandiera lyrata (ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 29 publications
1
27
0
Order By: Relevance
“…The measured PH, PW and FW values in treatments with NaCl concentrations of 25, 50 and 75 mM tended to be higher than those without salt application, supporting Niu and Rodriguez's assertion that Salvia has a relatively high tolerance for soil salinity. Most of the extant studies in which NaCl concentrations of 0, 50 and 100 mM were employed indicated that, while plants tolerate 50 mM NaCl, they start to suffer at 100 mM NaCl.…”
Section: Resultssupporting
confidence: 69%
“…The measured PH, PW and FW values in treatments with NaCl concentrations of 25, 50 and 75 mM tended to be higher than those without salt application, supporting Niu and Rodriguez's assertion that Salvia has a relatively high tolerance for soil salinity. Most of the extant studies in which NaCl concentrations of 0, 50 and 100 mM were employed indicated that, while plants tolerate 50 mM NaCl, they start to suffer at 100 mM NaCl.…”
Section: Resultssupporting
confidence: 69%
“…Urban landscape irrigation with alternative water sources such as municipal reclaimed water is common in arid and semiarid regions (Grieve, 2011). A potential problem of using reclaimed water is elevated salt levels, which adversely affects plant growth, development, and causes foliar salt injury on sensitive plants (Cai et al, 2014b;Niu et al, 2012a;Veatch-Blohm et al, 2014). Unlike fruits and vegetables where maximizing yield is the ultimate goal, the maintenance of good aesthetic appearance and blemishfree foliar tissue are important for ornamental plants (Niu and Cabrera, 2010).…”
mentioning
confidence: 99%
“…Many aster species have been studied for salt tolerance, and their responses to salinity are highly dependent on the species. Plains zinnia (Zinnia grandiflora) plants all died at an EC of 7.3 dS • m -1 , and chocolate daisy (Berlandiera lyrata) had low survival percentages and low foliar ratings at EC of 5.5 and 7.3 dS • m -1 (Niu et al, 2012a). Treasure flower (Gazania rigen), known as coastal gazania and naturalized on coastal dunes and roadsides in Australia, had 52.5% greater reduction of shoot DW at EC of 12 dS • m -1 compared with nonsalinized controls (EC of 0.8 dS • m -1 ), but had no other signs of stress or injury (Niu and Rodriguez, 2006).…”
mentioning
confidence: 99%
“…Reviews of several greywater studies indicate that Na concentrations of greywater range from 7.4 to 480 mgÁL -1 , whereas Cl concentrations range from 9 to 88 mgÁL -1 (Christova-Boal et al, 1996;Eriksson et al, 2002). Salinity tolerance research conducted on landscape plant species has commonly been conducted using simulated reclaimed wastewater (treated municipal effluent) (Marcotte et al, 2004;Miyamoto et al, 2004;Niu et al, 2007Niu et al, , 2012Wu et al, 2000).…”
mentioning
confidence: 99%